Solve π₯2π¦``β3π₯π¦`+5π¦=π₯2sin(πππ₯) ;π¦(1)=1,π¦`(1)=0
Solution;
This is a Cauchy Euler differential equation;
Substitute "x=e^t" hence t=ln(x)
"\\frac{dy}{dx}=\\frac{dy}{dt}\\frac{dt}{dx}=e^{-t}\\frac{dy}{dt}"
"\\frac{d^2y}{dx^2}=\\frac{d}{dx}(e^{-t}\\frac{dy}{dt})=-e^{-2t}\\frac{dy}{dt}+e^{-2t}\\frac{d^2y}{dt^2}"
Substitute in the given equation;
"e^{2t}(-e^{-2t}\\frac{dy}{dt}+e^{-2t}\\frac{d^2y}{dt^2})-3e^t(e^{-t}\\frac{dy}{dt})+5y=e^{2t}sin(t)"
Simplify;
"\\frac{d^2y}{dt}-4\\frac{dy}{dt}+5y=e^{2t}sin(t)"
Above equation is homogeneous;
The characteristic equation ;
"r^2+4r+5=(r-2)^2+1"
The roots are;
r=2+i and r=2-i
The homogeneous solution;
"y_h=e^{2t}(C_1cos(t)+C_2sin(t))"
The particular solution;
"y_p=t.(e^{2t}Acos t+e^{2t}Bsint)"
By distribution;
"y_p=te^{2t}(Acost+Bsint)"
Differentiating;
"y'_p=(2te^{2t}+e^{2t})(Acost+Bsint)+te^{2t}(-Asint+Bcost)"
Differentiate ;"y''_p=(4te^{2t}+4e^{2t})(Acost+Bsint)+(4te^{2t}+2e^{2t})(-Asint+Bcost)+te^{2t}(-Acost-Bsint)"
Substitute into the transformed equation and simplify;
"e^{2t}(-2Asint +2Bcost)=e^{2t}sint"
Equate the coefficients;
-2A=1;A=-0.5
B=0
Thefore;
"y_p=-\\frac12te^{2t}cost"
Since ;
"y=y_h+y_p"
The general solution of the equation is ;
"y=e^{2t}(C_1cost+C_2sint)-\\frac12te^{2t}cost"
Write in terms of x by replacing x=et;
"y=x^2(C_1cos(lnx)+C_2sin(lnx))-\\frac12x^2ln(x)cos(lnx)"
Apply the initial conditions to find the constants;
y(1)=1
1="C_1"
"y=x^2cos(lnx)+C_2x^2sin(lnx)-\\frac12x^2lnxcos(lnx)"
"y''=C_2(x^2sin(lnx)-\\frac{x^2lnxcos(lnx)}{2})+x^2cos(lnx)"
Use the condition;
y'(1)=0
0=C2(0+0)+0
C2=0
Hence;"y=x^2cos(lnx)-\\frac12x^2ln(x)cos(lnx)"
Comments
Leave a comment